Hanifsyah Rozi, Pakhrur Razi Identification of Extreme Rainfall in Padang Based on Weather Radar Imagery : Case Study Flood July 2023: Approach Using Weather Radar Data - rozi, hanifsyah (EarthCare, 2024)
Extreme rainfall combined with high impact weather frequently happens in the Padang city region, resulting in flooding, damaging livelihoods, and endangering lives and the environment. Consequently, the detection of intense precipitation patterns like convective cloud development, cloud distribution patterns, as well as the time and duration of rainfall needs to be analyzed to improve disaster mitigation and research development, especially in the Padang city area. In this study we processed gematronic brand weather radar data with volumetric format to produce several weather radar products to identify extreme rainfall that causes flooding. Based on our identification, the rain on July 13 to 14, 2023 has occurred from noon to early morning, detected convective clouds with reflectivity values reaching 55-60 dBZ which indicates light rain to extreme rain, with peak rain occurring in the afternoon and evening. Identifying the pattern and duration of extreme rainfall allows for better planning and risk mitigation measures.